Statistical models for predicting the number of under-five mortality in Nepal. - Madhav Kumar Bhusal; Shankar Prasad Khanal (PLoS ONE)
Background Nepal has experienced the glacial reduction of under-five mortality in recent years which portends greater challenges to achieve the global target outlined in the Sustainable Development Goals (SDGs) for reducing childhood mortality. To resolve this inevitable adversity and safeguard newborns' lives, additional scientific studies are necessary to plan for evidence-based interventions. Objective This study aimed to develop a suitable statistical model using the associated factors to predict the number of under-five mortality a mother in Nepal encountered throughout her lifetime. Methods The nationally representative Nepal Demographic and Health Survey (NDHS) 2022 data were used to conduct this study. The response variable was the number of under-five mortality a mother has experienced throughout her lifetime. Factors related to different circumstances, including maternal, paternal, socioeconomic, child, environmental, and the utilization of health care services were considered as independent variables. The zero-inflated negative binomial regression (ZINBR) model was fitted as the most plausible model to analyze the number of under-five mortality by its covariates after assessing the different count models including the Poisson regression (PR) model, negative binomial regression (NBR) model, zero-inflated negative binomial regression (ZINBR) model, and hurdle negative binomial regression (HNBR) model. Results The analysis of the data revealed that 8.6% of the mothers in Nepal have endured at least one under-five mortality. The mean number of deaths before attaining five years was found to be 0.11 (95% CI: 0.10-0.11). The ecological region, smoking habit of mothers, total CEB, source of drinking water, preceding birth interval, and birth order number were obtained as significant covariates of the number of under-five mortality. Mothers from the mountain region (IRR: 1.1756, 95% CI: 1.0095-1.369, p-value = 0.0418) in contrast to hilly region, smoker mothers (IRR: 1.2067, 95% CI: 1.0392-1.4011, p-value = 0.0141) as compared to non-smoker mothers, mothers with total CEB 3 or more (IRR: 1.588, 95% CI: 1.3116-1.9226, p-value = 0.0353) as compared to 2 or less, preceding birth interval less than 24 months (IRR: 1.2061, 95% CI: 1.0788-1.3485, p-value = 0.0018) as compared to 24 months or more, and birth order number 4th or above (IRR: 3.5681, 95% CI: 3.1512-4.0401, p-value < 0.001) as compared to 1st-3rd were associated with the increased incidence of number of under-five mortality. Furthermore, the mothers who drink water from the tube well (IRR: 0.7719, 95% CI: 0.6191-0.9623, p-value = 0.0323) as compared to those who drink water from other sources have a decreased incidence of the number of under-five mortality. Conclusions The ecological region, mother smokes cigarettes, total CEB, source of drinking water, preceding birth interval, and the birth order number appeared as the important predictors of under-five mortality. The high under-five mortality prevalent in the mountain and terai areas of Nepal presents a significant hurdle in efforts to decrease overall under-five mortality. Thus, improving existing healthcare services, raising the quality of life, and introducing effective health education initiatives are crucial to reducing under-five mortality.